Inovasi Kurikulum Pembelajaran Akidah Akhlak: Analisis Terhadap Penguatan Moderasi Beragama Dan Kesadaran Ekologis - Maesaroh; Muh. Wasith Achadi (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2026)
This study is grounded in the urgency of transforming Akidah Akhlak learning in response to the challenges of intolerance, moral degradation, and environmental crises. Previous studies have generally treated religious moderation and ecological awareness as separate domains, resulting in limited curriculum innovations that integrate both perspectives. This study aims to analyze curriculum innovation in Akidah Akhlak learning at MAN 4 Bantul and its contribution to character development through religious moderation and ecological awareness. The research employed a qualitative approach using a case study design. Research participants consisted of the vice principal for curriculum affairs, Akidah Akhlak teachers, and students at MAN 4 Bantul. Data were collected through in-depth interviews, classroom observations conducted over one week for two hours each day, and analysis of curriculum documents and instructional materials. Data validity was ensured through source triangulation, technique triangulation, and member checking. Data analysis was carried out interactively through data reduction, data display, and conclusion drawing. The findings indicate that curriculum innovation was implemented through the integration of religious moderation values, the application of project-based learning, and the strengthening of ecological dimensions in both classroom learning and madrasah culture. The study further suggests that Akidah Akhlak learning not only internalized the values of tolerance, anti-extremism, and respect for diversity, but also fostered environmental responsibility through waste management activities, school greening programs, and religious reflection based on ecological awareness. The integration of moderation- and ecology-based learning contributed to increased student engagement and supported the development of tolerant attitudes, critical thinking, social responsibility, and environmental awareness. This study recommends a more systematic strengthening of Akidah Akhlak curriculum policies based on religious moderation and ecological awareness in madrasahs.